Penggunaan Coaching Model GROW ME untuk Meningkatkan Keterampilan Manajemen Kelas Guru Kelas I - Veronica Franciska Sabandar; Eka Desy Purnama; Januar Heryanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to improve the classroom management skills of first grade teachers at SD Lentera Harapan Tolikara through the implementation of the GROW ME coaching model (Goal, Reality, Options, Will, Monitoring, Evaluation). Classroom management is a key element in creating a conducive and effective learning environment. The GROW ME coaching model is applied to help teachers design and achieve more effective goals in classroom management. This research uses the Action Research method with a cyclical approach consisting of planning, implementation, observation, and evaluation stages. The subjects of the study consist of two first-grade teachers who actively participated in the coaching process. The results show a significant improvement in the classroom management skills of both teachers. In the first cycle, classroom management scores increased by 43% and 48%, and in the second cycle, they rose to 52% and 69%, exceeding the success target set at a minimum of 40%. Based on these findings, it can be concluded that the GROW ME coaching model is effective in improving teachers' classroom management skills, leading to a more effective and conducive learning atmosphere. It is hoped that the school will continue the implementation of the GROW ME coaching model to support the professional development of teachers.